Biogeographic assessment and evaluation of various vegetation landscapes in the Mediterranean Region of Chile for their administration and organization - P. J. Lozano Valencia; J. A. Cadiñanos (Boletín de la Asociación de Geógrafos Españoles, 2015)
Texto resumen